A Dialogue on the Role of Muslim Women in the Development of Healthy Economy in Islamic Civilization - Sadatmoosavi, Zohreh (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2016)
A substantial theme has been encountered by all national policies and plans in the 1990s, with raising the concept of Gender and Development (GAD). This is the time to regard to cultural elements of economic system in the postmodern era as some scholars have tried to defend from green, health and pure economies. Specifically, with the development of concept and empowerment’s of global implications, examination on the position of Islamic economy is required. Women due to their tasks in family, potentially have enjoyed some income sources such as; alimony, dower (mahr) and inheritance. In addition, they can improve their economic status by enhancement on the level of their education and career. Since today, economic and cultural dominance of the West has influenced the Muslim’s life style, more than before we need to return to Islamic culture and its adaptation to today’s condition. As the objective of study this paper attempts to regard the role of women in Islamic economy.